Liver Transplant for Unusually Large Polycystic Liver Disease: Challenges and Pitfalls - Pablo Serrano Rodriguez; Alfred Sidney Barritt IV; David Allen Gerber; Chirag Sureshchandra Desai (Case Reports in Transplantation)
Patients with polycystic liver disease are described in the literature as both recipient and donor for liver transplant. Due to well-preserved liver function, it is often difficult for these patients to receive an organ. Livers of these patients are often large and heavier than a normal organ. We describe two cases who had exceedingly large livers, weighing 14 and 19 kg. To the best of our knowledge and search, these are some of the heaviest explanted livers, and one of the patients incidentally received a liver from a donor with ADPKD. The aim of this report is to discuss the challenges and pitfalls of evaluating and listing, technical aspect of the transplant, possibility of transplanting a liver from a donor with a genetic cystic disease to a cystic disease recipient, and the related literature with some highlights on the facts from UNOS/OPTN data.